Preparation and Characterization of ZnO Nano-Structured Thin Films - Singh, Nagendra Pratap (My University, 2008)
Zinc Oxide has a wide range of properties that depends on doping, process parameters, fabrication methods and thickness of the thin films. The properties of zinc oxide include high transparency, piezoelectricity, wide band-gap semi-conductivity, room temperature ferromagnetism and huge magneto-optic and sensing properties. We can obtain the different nano-structures of ZnO by changing the process parameters in thermal evaporation system. We have fabricated thermal evaporation system by designing and assembling the components to achieve high vacuum. We have achieved the vacuum of 10-6 m bar. We have deposited ZnO thin film by taking ZnO powder (MERK 99.98%) and deposited on the properly cleaned glass substrate directly evaporating powder in the chamber. Deposited thin film was annealed at the temperatures 4500C, 5000C, 5500C and 6000C. The thickness and band-gap of the thin films was 334.09nm and 3.25eV measuring by UV/VIS Spectrophotometer. The XRD peaks reveal that the crystallinity improves with the annealing temperature. The surface morphology, surface roughness and adhesion properties have been studied by the Atomic Force Microscope (AFM). Adhesion property on glass substrate improves with annealing temperature. The grain size increases with increase in annealing temperature. The surface roughness changes with annealing temperature and observed highest at 5500C (Ra=444.558nm) with RMS value 516.230nm.
M.Tech (Mat. Sc.)
Keywords: ZnO; Nano structured; Thin Films